Kajian Teologis Kitab Ayub 1-2 Dan Implikasi Psikologis Terhadap Keluarga Kristen Yang Mengalami Kematian Anak Di Gereja Toraja Klasis Makale Tengah Jemaat Imanuel Tampo - Windy Windy (KAMASEAN: Jurnal Teologi Kristen, 2020)
This paper is motivated by a Christian family at Gereja Toraja Jemaat Imanuel Tampo who mourn the death of a child. The death of child causes parents to give different emotional reactions from one to others. Job 1-2 show that how Christians confronting with suffering. This is the  author’s consideration to see the theological study of Job 1-2 and its implications for Christian families who experience child death at Gereja Toraja Klasis Makale Tengah Jemaat Imanuel Tampo. The research method that the authors use in this research is a narrative study qualitative. This narrative study is developed to describe the theological studies of Job 1-2 and the implications for Christian family who experience child death at Gereja Toraja Klasis Makale Tengah Jemaat Imanuel Tampo. Job confronted the suffering that occurs by surrendering to God and accepts that suffering humbly. Job 1-2 teaches to understand God’s sovereignty that occurs through suffering. Christian families who grieve over the loss of their children also accept the suffering they endure. Theory of Kubler Ross regards 5 stages of grief, namely denial of anger, bargaining, depression, and acceptance as a process to be accepted the suffering. In the end the Christian family in the Gereja Toraja Klasis Makale tengah Jemaat Imanuel Tampo can through the suffering of the death of a child by surrending to God and accepting it.